THE ROLE OF HISTORICAL CONSCIOUSNESS IN SHAPING COLLECTIVE SOCIAL THINKING: A YOUTH-CENTERED APPROACH (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This study examines the role of historical consciousness in shaping collective social thinking, with a particular focus on youth as a dynamic and transformative social group. The research conceptualizes historical consciousness as a multidimensional construct encompassing cognitive, axiological, and reflective components that influence how individuals interpret the past and relate it to present and future societal processes. Using an interdisciplinary methodological framework, the study analyzes the interaction between historical consciousness and collective social thinking within educational and socio-cultural contexts. The findings indicate that the development of historical consciousness among youth significantly contributes to the formation of critical thinking, social responsibility, and value-oriented perspectives. The paper argues that modern pedagogical strategies, including interactive learning and digital tools, are essential for fostering a deeper and more analytical form of historical understanding. The study concludes that strengthening historical consciousness is a key factor in ensuring sustainable intellectual and social development in contemporary societies.